Chemoreception and vertical movement in planktonic yolk-sac larvae of red sea bream Pagrus major - Tanaka, Yuuzi; Mukai, Yukinori; Takii, Kenzi; Kumai, Hidemi (Wiley-Blackwell, 1991)
The capability of planktonic yolk-sac larvae of red sea bream Pagrus major in detecting food was examined in the laboratory to ascertain basic knowledge on the early life history of this marine fish. After infrequent vertical burst swimming followed by slight rising or sinking, the larvae remained motionless within thin layers of concentrated food extract (rotifer, Brachionus plicatilis). At the moment of hatching, the larvae already have receptor cells with several cilia arranged radially in their open nostrils. Thus it is likely that by means of their vertical movement they are capable of sensing the thin food patch layer. We suggest that planktonic larvae of Pagrus major are capable of detecting and remaining within food patches even before the onset of feeding. The onset of food detection in the earlier stages may be, to some extent, the more efficient strategy for larval survival and growth because this ability could contribute to a reduction in energy consumption.